FIRST LINE ANTI-TUBERCULOSIS DRUG RESISTANCE PATTERN IN MULTIDRUG-RESISTANT PULMONARY TUBERCULOSIS PATIENTS CORRELATE WITH ACID FAST BACILLI MICROSCOPY GRADING - Soedarsono, Soedarsono; Mertaniasih, Ni Made; Sulistyowati, Titiek (Indonesian Journal of Tropical and Infectious Disease, 2020)
Multidrug-resistant tuberculosis (MDR-TB) is a global public health crisis. Acid-fast bacilli (AFB) gradation in sputum examination is an important component in Pulmonary Tuberculosis (PTB) diagnosis and treatment outcome monitoring. Previously treated pulmonary TB patients with a higher AFB smear gradation may have higher rates of acquired resistance. Patients with a higher AFB grade indicate a higher bacillary load and had higher rates of acquired resistance. This study aims to evaluate the correlation between AFB gradation and first-line anti-TB drug resistance patterns in MDR pulmonary TB patients. This was a retrospective study conducted from August 2009 to April 2018 in Dr. Soetomo Hospital. Sputum samples were taken from MDR PTB patients. Sputum smear examination was done using Ziehl–Neelsen staining and gradation was measured according to IUATLD criteria. Samples with positive smear were evaluated for resistance patterns based on culture and resistance tests using the MGIT 960 BACTEC System. There were 433 sputum samples with AFB positive collected from MDR PTB patients. Resistance to RHES was found in 22 (14%) AFB +1, 19 (15%) AFB +2, and 29 (20%) AFB +3. Resistance to RHS was found in 22 (14%) AFB +1, 12 (9%) AFB +2, and 13 (9%) AFB +3. Resistance to RHE was found in 39 (25%) AFB +1, 38 (29%) AFB +2, and 35 (24%) AFB +3. Resistance to RH was found in 74 (47%) AFB +1, 61 (47%) AFB +2, and 69 (47%) AFB +3. Statistic analysis by Spearman test showed that there was no significant correlation between AFB gradation and first-line anti-TB drug resistance patterns. Acquired resistance to RHES can also found in lower bacillary load AFB +1.